2017
DOI: 10.1097/ncc.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Symptom Management Intervention

Abstract: Background Little is known about cancer patient and family caregiver preferences for the content and format of non-pharmacologic interventions. Revising interventions based on patient and caregiver feedback before implementation may improve intervention feasibility and acceptability, especially in the context of advanced cancer. Objectives To obtain feedback from advanced, symptomatic lung cancer patients and their family caregivers on the content and format of a non-pharmacologic symptom management interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In line with lung cancer patient and caregiver preferences for intervention delivery, the telephone intervention was acceptable. 21 As more and more supportive care is being delivered to caregivers by phone, and caregivers also desire more support by phone, there is a need for both clinicians and research personnel to develop better phone skills to improve interactions with caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with lung cancer patient and caregiver preferences for intervention delivery, the telephone intervention was acceptable. 21 As more and more supportive care is being delivered to caregivers by phone, and caregivers also desire more support by phone, there is a need for both clinicians and research personnel to develop better phone skills to improve interactions with caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study with lung cancer patients and caregivers revealed a desire for educational interventions that focus on adverse effects and the provision of various coping skills. 21 Similarly, in a palliative care intervention study for lung cancer caregivers, which had a significantly positive impact on caregiver quality of life, symptom management strategies were a top priority across the four educational sessions of the quality of life intervention. 26 Findings in this pilot study suggest that caregiver education should include attention to communication skills in order to combine both knowledge needs for symptom management as well as communication skills to aid in coping with symptom management responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Patient inclusion criteria included: 1) age ≥ 18 years; 2) at least 3 weeks post-diagnosis of lung cancer; 3) at least moderate severity for one or more symptoms at recruitment, including: anxiety, depressive symptoms, pain, fatigue, or breathlessness; 4) a consenting family caregiver; and 5) adequate English fluency. Patient exclusion criteria included: 1) significant psychiatric or cognitive impairment; 2) previously providing feedback on the intervention; 23 3) current participation in another psychosocial study; or 4) receiving hospice care. Caregiver inclusion criteria included: 1) age ≥ 18 years; 2) living with the patient or visiting regularly; and 3) adequate English fluency.…”
Section: Methodsmentioning
confidence: 99%
“…Caregiver inclusion criteria included: 1) age ≥ 18 years; 2) living with the patient or visiting regularly; and 3) adequate English fluency. Caregiver exclusion criteria included: 1) current participation in another psychosocial study; 2) previously providing feedback on the intervention; 23 or 3) significant psychiatric or cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
“…This could be attributable to the fact that the scopes of these studies differ greatly. Most of them have an emphasis on a particular goal, such as a specific patient group ( Hirose et al, 2005 ; Hirose et al, 2009 ; Schmidt et al, 2017 ), specific treatment ( Peeters et al, 2012 ) or specific interest in characteristics such as emotional wellbeing ( Mosher et al, 2017 ). In contrast, the present qualitative study aimed to identify patient-relevant lung cancer treatment characteristics across different therapies (including newer types of therapies such as immunotherapies) according to advanced lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%